A novel proposal to improve fairness in TCP Reno. (1st December 2008) - Tan, Liansheng; Yang, Peng
The fairness in TCP Reno has been long known as unsatisfactory as it gives more bandwidth shares to short flows while starves the long flows. In this paper, a new proposal to improve fairness in TCP Reno is presented. We describe the bandwidth allocation among TCP Reno flows into a new utility optimised problem, in which the requirement of fairness among flows is taken into account in the constrain conditions. This problem is then solved by the Karush-Kuhn-Tucker (KKT) condition to achieve a new distributed algorithm to allocate bandwidth among flows with fairness being enhanced. On this basis, we discuss the implementation of this algorithm in the packet level for real networks using the technique of differential dropping in routers. Simulation results show that the new proposal regulates the bandwidth share effectively and improves the fairness performance of TCP Reno.